Ta'alluq, Takhalluq dan Tahaqquq sebagai Proses Meningkatkan Kualitas Jiwa Manusia - Agus Ali; Nurwadjah Ahmad EQ; Andewi Suhartini (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2022)
In improving the quality of one's soul there are three stages that are carried out. First, doing Dhikr or Ta'alluq on God, that is, one must try to remember and bind the consciousness of the heart and mind to Allah. Wherever a Muslim cannot be free from dhikr and thinking). Second, Takhalluq, a person consciously imitates the attributes of God so that a believer has noble qualities as His attributes. This process can also be referred to as the process of internalizing the nature of God into human beings. In this regard, the Sufis usually rely on the Hadith of the Prophet which reads, "Takhallaqu bi akhlaqi Allah". Third, tahaqquq, that is, a person must be able to actualize his awareness and capacity as a believer or religious person who himself has been "dominated" by the attributes of God so that it is reflected in his pure and noble behavior.